The Impact of Bullying on Students’ Learning Motivation: A Study of Engineering Students at Universitas Pelita Bangsa - Mulyana, Nanang; Hisniati, Sally Badriya; Maryati, Maryati (Journal Corner of Education, Linguistics, and Literature, 2026)
Bullying has increasingly become a critical issue in higher education, with potential consequences for students’ psychological well-being and academic engagement. This study aims to examine the effect of bullying on students’ learning motivation at the Faculty of Engineering, Universitas Pelita Bangsa. A quantitative approach with an associative research design was employed. Data were collected from 111 undergraduate students using a structured questionnaire measured on a five-point Likert scale. The instruments were tested for validity using Pearson product–moment correlation and for reliability using Cronbach’s Alpha. Data analysis was conducted through descriptive statistics and simple linear regression. The results indicate that bullying has a negative and statistically significant effect on students’ learning motivation (β = –0.177; p < 0.05). The coefficient of determination (R² = 0.039) shows that bullying explains 3.9% of the variance in learning motivation, while the remaining variance is influenced by other factors not examined in this study. These findings suggest that although learning motivation is shaped by multiple determinants, bullying remains an important social factor that can undermine students’ academic motivation. The study highlights the managerial importance of creating a safe and supportive campus environment through clear anti-bullying policies, accessible reporting mechanisms, and strengthened student support services. Despite limitations related to sample scope and self-reported data, this research contributes empirical evidence to the literature on bullying in higher education and provides practical insights for university management in enhancing students’ learning motivation.